Kepercayaan, Komitmen, Kedekatan Pelanggan dan Loyalitas Pelanggan dalam Hubungan Perbankan Syariah: Studi Kasus Bank Syariah Indonesia (BSI) - Yusuf, Abdurrahman Maulana; Wahyuningsih, Adityas (JURNAL ILMIAH FEASIBLE: Bisnis, Kewirausahaan dan Koperasi, 2024)
This study aims to examine the relationship between trust, commitment, customer intimacy, and customer loyalty in the context of Islamic banking. This case study is focused on Bank Syariah Indonesia (BSI). The research method used was a survey through questionnaires distributed to 100 customers of Bank Syariah Indonesia. The data obtained were then analyzed using PLS (Partial Least Square) analysis to examine the relationship between trust, commitment, customer intimacy, and customer loyalty. The results of the study show that trust, commitment, and customer intimacy have a significant relationship with customer loyalty. The results of this study can be used as a guide for Bank Syariah Indonesia in developing strategies to maintain and increase customer loyalty.